Association and diagnostic utility of diastolic dysfunction and myocardial fibrosis in patients with Fabry disease. Issue 2 (12th July 2018) - Liu, Dan; Oder, Daniel; Salinger, Tim; Hu, Kai; Müntze, Jonas; Weidemann, Frank; Herrmann, Sebastian; Ertl, Georg; Wanner, Christoph; Frantz, Stefan; Störk, Stefan; Nordbeck, Peter
Abstract : Objectives: Current guidelines highlight important therapy implications of cardiac fibrosis in patients with Fabry disease (FD). However, association between morphological and functional impairments with cardiac fibrosis in hereditary cardiomyopathies remains elusive. We investigated the association between echocardiography-determined cardiac dysfunction and cardiac MRI (cMRI)-detected myocardial fibrosis (late gadolinium enhancement, LE) in patients with FD with preserved left ventricular ejection fraction (≥50%). Methods: 146 patients with FD (aged 39±14 years, 57 men) were analysed, all receiving echocardiography and cMRI within a 1 week interval. Longitudinal systolic strain (LS_sys), strain rate (LSr_sys) and diastolic strain rate (LSr_E/LSr_A) were assessed using speckle-tracking imaging. Receiver operating characteristic (ROC) analysis was performed to identify the diagnostic performance of various markers for LE. Results: LE was detected in 57 (39%) patients with FD. LV wall thickness, left atrial volume, septal E/e′, diastolic dysfunction grade, global LS_sys and E/LSr_E, mid-lateral LS_sys and LSr_E, as well as N-terminal pro-brain natriuretic peptide were all associated with LE independent of age, sex, body mass index, New York Heart Association functional class and kidney function. In ROC curve analysis, septal E/e′ performed best (area under the curve=0.86, 95% CI=0.79 to 0.92). Septal E/e′>14.8 was strongly associated with LE (specificity=97.8% and sensitivity=49.1%). In 9% of patients, localised LE was present even though no other cardiac or kidney abnormalities were detected. Conclusions: Echocardiography-derived diastolic dysfunction is closely linked to LE in FD. Septal E/e′ ratio is the best echocardiographic marker suggestive of LE. Diastolic dysfunction is not a prerequisite for LE in FD, since LE can be detected in the absence of measurable cardiac functional impairments. Trial registration number: ClinicalTrials.gov Identifier (NCT03362164 ).